Peran KPPM dalam Membantu Meningkatkan Pendidikan Anak di Desa Patane II - Lidya Elisca Siahaan; Patrycia Hutapea; Yoel Tambunan; Prayer Gultom; Putra Lumbantoruan; Atalisi Zalukhu (Lembaga Pengembangan Kinerja Dosen, 2025)
Access to education that is close and affordable is a major obstacle in Patane II Village, Access to education that is close and affordable is a major obstacle in Patane II Village, Porsea District, Toba Regency. Because there are no schools in the area, children have to go to other villages to study, which has an impact on their physical condition, study time, and safety. Excessive use of electronic devices also has a negative impact on children's learning efforts. The purpose of this study is to analyze the challenges of education in the area and offer community-based solutions involving the government, community, and the use of technology. This study identifies various approaches to tutoring and research related to children's schools. The qualitative methods used are direct observation and interviews. The results of the study indicate that community-based solutions can effectively and sustainably improve access to education. Through the Student Service Practice Lecture Program (KPPM), children's interest in education has increased, especially in mathematics and English. In addition, students' social interactions with children help them reduce their dependence on electronic devices and increase awareness of the importance of education. Further collaboration is needed between the government, community, and educational institutions to achieve long-term goals, such as further school construction, improving teacher quality, and monitoring the use of electronic devices to increase children's learning opportunities.